2017
DOI: 10.1159/000484662
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Lung Adenocarcinoma with Marked Improvement of Pulmonary Lymphangitic Carcinomatosis by Adding Bevacizumab to Cisplatin and Pemetrexed

Abstract: A 40-year-old man with a diagnosis of lung adenocarcinoma (cT4N3M1c, stage IVB) experienced worsening of lymphangitic carcinomatosis in the right lung and right pleural effusion after receiving 1 cycle of first-line chemotherapy consisting of cisplatin and pemetrexed. Bevacizumab was thus added from the second cycle of the cisplatin-pemetrexed regimen, leading to a marked improvement in pulmonary lymphangitic carcinomatosis and a decrease in pleural effusion. Subsequently, maintenance therapy consisting of pem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
2
Order By: Relevance
“…PLC in lung cancer has been realized as a marker of disseminated disease with a poor response to chemotherapy (21,22). Although combination chemotherapy prolonged OS in a reported case with PLC confined to a different ipsilateral lobe (23), the prognosis is generally very poor (median survival 2-13 months) and has not improved much over time (24,25). These results suggested that the prognosis of PLC may vary by histology of the tumor and the definition of PLC.…”
Section: Discussionmentioning
confidence: 95%
“…PLC in lung cancer has been realized as a marker of disseminated disease with a poor response to chemotherapy (21,22). Although combination chemotherapy prolonged OS in a reported case with PLC confined to a different ipsilateral lobe (23), the prognosis is generally very poor (median survival 2-13 months) and has not improved much over time (24,25). These results suggested that the prognosis of PLC may vary by histology of the tumor and the definition of PLC.…”
Section: Discussionmentioning
confidence: 95%
“…This was also indicated by the improvements in the mPFS and mOS in the Anlotinib group compared to those in the Other group ( Figure S3 ). Moreover, after reviewing previously reported cases ( 11 13 , 29 , 30 ), we calculated an ORR of 50% in gefitinib-treated patients with EGFR mutations ( 12 ), which was 100% in our study ( Table 2 ). Apatinib-based treatment was reported to demonstrate a DCR of 69.2%, mPFS of 5.2 months, and mOS of 10.2 months ( 7 ) when not distinguishing patients’ baseline characteristics, treatment lines and strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan çalışmalarda kanserli hastalarda görülme oranının %1'in altında olduğu bildirilmekle beraber, görülme oranının %6 ile 8 arasında değiştiğini bildiren çalışmalar da vardır. 2,4,13,14 Bizim çalışmamızda LK görülme oranı %8 idi ve literatür ile uyumluydu.…”
Section: Lenfanji̇ti̇s Karsi̇nomatozanin Tanisiunclassified
“…nin antegrad yoldan akciğer lenfatikleri boyunca yayılabileceği veya akciğerin vasküler yapılarından tümöral embolilerin ekstravazasyon ile lenfatikleri infiltre etmesi ile LK'nın ortaya çıkabileceği de ileri sürülmüştür. 1,2 Hangi yolla olursa olsun sonuç olarak tümör hücrelerinin lenfatik sistemin düşük basınçlı özelliğinden dolayı tutunmaları ve çoğalmaları nispeten kolay olduğu ve malign tümör hücrelerinin ürettiği vasküler endotelyal büyüme faktörünün (VEGF) etkisi ile tümör hücreleri perilenfatik peribronşial bağ dokusunun infiltrasyonunun hızlanacağı öne sürülmektedir. 3,4 Radyolojik olarak klasik görünüm peribronkovasküler-interlobüler düzensiz, nodüler kalınlaşmalardır.…”
unclassified